Uretrorenoscopy laser lithotripsy treatment of stones impacted in the left ureter 10 years after right kidney autotransplantation - Milović, Novak; Bančević, Vladimir; Teodorović, Goran (Vojnosanitetski pregled, 2014)
Introduction. Urinary tract calculosis is a very common condition in general population. It appears in 5–10% of population, and can be managed conservatively or by minimally invasive, endoscopic and surgical procedures or extracorporeal shock way lithotripsy. Lesions of the ureter can be resolved by JJ stent insertion, end-to-end anastomosis, ureterocystoneostomy, percutaneous nephrostomy, nephrectomy, intestinal graft interposition or kidney autotransplantation. Case report. We presented surgical treatment and outcome in a female patient, with a large defect of the right ureter due to impacted stone treatment, following a successful autotransplantation of the right kidney. Ten years later a stone impacted in the left ureter was successfully treated by ureterorenoscopy and laser lithotripsy. Asynchronously combined kidney aoutotransplantation and ureterorenoscopic lithotripsy preserved kidney function. Conclusion. Bilateral organs preservation should be considered even in the absence of malignancy, especially in younger population.
Keywords: ureterolithiasis; lithotripsy; laser; transplantation; autologous; kidney